90 Eye donation in the hospice setting: personal and system-based barriers to discussing this end of life option with patients and family members: an exploratory qualitative study. (14th March 2023) - White, Alice; Long-Sutehall, Tracy
Abstract : Background: In the UK there is a national shortage of corneas available for transplantation. Up to 50% of patients within a palliative care setting may be eligible to donate corneas, yet donation rates from this environment are low. Studies have indicated that healthcare professionals are reluctant to initiate conversations. Doctors views on donation are poorly represented in the literature. Aim: To identify and explore barriers to clinicians initiating conversations about the option of eye donation as part of end of life care planning in a hospice setting. Methods: An exploratory qualitative design was adopted using focus groups. The study was based from palliative care services in the South of England and was conducted between 15thand 22nd February 2017. Participants included 14 doctors holding registrar, specialty doctor or consultant posts. Qualitative content analysis was the data analysis method chosen. Results: Despite holding positive views towards corneal donation, doctors are unlikely to initial conversations. Barriers identified included 1) lack of knowledge around eye donation, principally involving eligibility 2) attitudes, influenced by personal beliefs but also clinical experiences and the perception of patient and public views on donation in a hospice setting 3) professional concerns about workload and the prioritisation of significant conversations, and 4) a lack of confidence in the process of eye donation which directly impacted on an individual initiating a discussion. Findings indicate that level of clinical experience does not influence the likelihood of initiating conversations, but individual experiences do shape attitudes. The hospice was viewed as a unique entity with specific challenges to implementing corneal donation services. Conclusions: Despite positive views toward eye donation, many barriers contribute to a lack of confidence in the system and low donation rates. Improvements could be made by education and support for staff members and appointing a designated lead staff member.